Punjab breathes better: yoga’s role in mental health revolutions - Mishra, Kamlesh Kumar; Jha, Amresh Kumar; Goyal, Alka; Goyal, Ekram; Dhakad, Gagan Singh (International Journal of Research in Medical Sciences, 2026)
Background: Due to exhausting fast pace of life, stress has become an integral part of our lives. It further leads to various physical and psychiatric disorders. Contrarily Yoga has been proven to be beneficial in improving our overall health. Doing a non-psychopharmacological intervention like Yoga alone in people have stress, depression, anxiety and insomnia in Mohali having ‘C.M di Yogshala (CMDY)’ initiative. CMDY is being run by the Guru Ravidas Ayurveda University, Hoshiarpur (GRAU), Govt of Punjab. To see the efficacy of Yoga in people coming to CMDY in Mohali having stress, depression, anxiety and insomnia. Methods: 120 individuals suffering from depression, anxiety, stress and insomnia were consecutively enrolled in study from Mohali having CMDY. DASS-21 (21 itemed depression, anxiety and stress scale) was applied to diagnose depression, anxiety and stress. To diagnose insomnia, Insomnia Severity Index (ISI) was used. To further confirm diagnosis of depression, anxiety and insomnia, International Classification of Diseases 10th edition for mental health and behavioral disorders (ICD-10) was used. For confirming stress, serum cortisol levels were analyzed. Above mentioned scales were applied at baseline and at 3 months after intervention is over. Yogic intervention was provided by trained Yoga instructors daily for 1 hour for 3 months. Data was analyzed statistically on SPSS-22.0. Results: 16 individuals out of 120 dropped out. 104 individuals followed back till the end of the study. There was significant reduction in DASS-21 score after 3 months of yoga. Serum cortisol levels also decreased from baseline after 3 months. Conclusion: This study concluded that yoga reduces severity of depression, anxiety and stress.